Reorienting Medical Dispute Resolution: MDP, ADR, and Litigation - Muhammad Darwis; Anatolijs Kriviņš; Abbas Ibrahim Al-Maliki (JUSTISI, 2026)
The aim of this study is to analyze the structure of the medical dispute resolution mechanism as stipulated in Law No. 17 of 2023 on Health and to examine its implications for the legal protection of patients, medical personnel, health workers, and health care facilities. The methods used in this study include a normative legal approach, incorporating both a statutory and conceptual framework, through a systematic review of Law No. 17 of 2023 on Health, Government Regulation No. 28 of 2024, Ministry of Health Regulation No. 3 of 2025, Ministry of Health Regulation No. 4 of 2025, Constitutional Court Decision No. 156/PUU-XXII/2024, and relevant scientific literature. The novelty of this research lies in the formulation of the Multi-Layer Medical Dispute Resolution Model, which integrates the identification of medical incidents, complaints and clarifications, disciplinary enforcement by the Professional Disciplinary Council, alternative dispute resolution, and the potential for administrative, civil, and criminal liability into a single normative framework. The results of the research indicate that prioritizing out-of-court dispute resolution mechanisms forms a multi-layered model oriented toward dialogue, professional evaluation, and redress; however, its effectiveness is largely determined by the clarity of procedures, the capacity of dispute resolution institutions, and the guarantee of balanced access for the parties so that legal protection and access to justice are realized proportionally. The conclusion emphasizes that the normative design of the Health Law has the potential to strengthen legal protection in the field of medical disputes, provided it is accompanied by the strengthening of subsidiary regulations, institutional frameworks, and implementation practices that ensure non-litigation mechanisms truly serve as corrective and restorative measures, rather than mere procedural formalities that hinder the fulfillment of the parties’ legal rights.